MODEL PEMBERDAYAAN TKI PASCA MIGRASI MELALUI EKONOMI PRODUKTIF MENUJU KELUARGA SAKINAH - Abas, Sayid; Widyahseno, Bambang; ., Rudianto (Universitas Muhammadiyah Ponorogo, 2014)
TKI post-migration becomes an important phenomenon that needs to get noticed intensively both from the government and society at large. Their return from abroad in addition to providing a positive contribution both for themselves, their families, and government. Due to the presence of migrants remittances of money increases so drastically. But a new problem arises, namely the workers did not have any postmigration activities that lead to improvements in the productive economy. Their income from abroad is used for unqualified consumptive needs. Through this research is expected to empower workers carry out postmigration economic development through productive ventures to materialize sakinah family. In particular, this study aims to 1) change the pattern of the workers think the post-migration from consumer culture to be productive by converting mental labor to employers, 2) economic empowerment of the workers productive post-migration and family education sakinah, 3) create a model of post-migration through the empowerment of migrant workers sakinah productive economy and family. The research was conducted in Ponorogo, East Java Province. The selection is based on considerations of the high number of migrants after migration in this area as well as the efforts to improve the quality of a productive economy. The method used by triangulation techniques, the method combined qualitative with quantitative methods. The analysis of secondary data using descriptive domain analysis techniques, taxonomy, Componential. The results of this study in the form of modules that will be applied to the empowerment of workers after the migration is, first, the modules of the changing patterns of the workers think the mental postmigration of workers into entrepreneurs; Second, entrepreneurship education and training modules; Third, education and training modules to build sakinah families according to the concept of religion.